Karakteristik fisikokimia dan organoleptik beras analog tepung komposit pedada, tepung garut, tepung kedelai dengan gliserol monostearat - Saraswati, Avina Rachma; Jariyah, Jariyah; Wicaksono, Luqman Agung (ARGIPA (Arsip Gizi dan Pangan), 2025)
Analog rice as an alternative reduces people's dependence on rice. The materials for this research were arrowroot tuber flour, pedada fruit flour, soybean flour, and various concentrations of glycerol monostearate (GMS). This research aims to study the effect of the proportion of arrowroot flour: pedada fruit flour: soybean flour and the addition of GMS on the physicochemical and organoleptic quality of analog rice, so produced with good quality and is liked by consumers. The design in this research was a completely randomized design (CRD) with a factorial pattern with two factors. Factor I is the proportion of arrowroot tuber flour: pedada fruit flour: soybean flour (75%: 5%: 20%, 70%: 10%: 20%, 65%: 15%: 20%). Factor II is the addition of GMS concentration (0.5%; 1%; 1.5%). Data analysis used the ANOVA method at a confidence level of 95%, if there were differences between treatments continued with the Duncan test a = 5%, and organoleptic tests used the hedonic scale scoring method with data calculations using the Friedman method. The results showed that rice was analogous to the treatment with the proportion of arrowroot tuber flour: pedada fruit flour: soybean flour 65%: 15%: 20%. and the addition of 1.5% GMS is the best treatment with water content values ​​of 4.72%, ash 0.71%, fat 0.41%, protein 7.65%, carbohydrates 86.52%, starch 74.01%, amylose 25.43%, amylopectin 48.58%, kamba density 0.6 g/ml, rehydration power 38.45%, cooking time 305 seconds. Color organoleptic test 4.22; taste 6.26; aroma 5.02; texture 5.08 (like).